Conditional Optimization of Single Cell Protein Production from Crude Oil by Pseudomonas aeruginosa - Haider, Mustafa; Rages, Ashraf; Al-Mergany, Huda (Science Publishing Group, 2024)
The study was carried out to investigate the possible biodegradation of crude oil as a carbon by the bacterium Pseudomonas aeruginosa isolated from marine environment (Ras El-Menkar- Benghazi- Libya) using basal yeast extract protease peptone-3 (BYP) enriched medium. The isolated bacterium was identified and characterized according to its cultural condition and microbial biochemical properties. Different experiments were developed throughout this study to stimulate bacterial growth and production of single cell protein (SCP). The results show that the optimal concentration of crude oil as a carbon source for the highest bacterial growth (1.14g/l), and production of SCP (0.65g/l; 57.02% of the biomass dry weight) was 1%. This was required to utilize up to 50.6% of oil as a carbon source. As to the nitrogen source, the optimal concentration of ammonium chloride was 0.1%, in which the bacterial growth and SCP production increased to 1.23 g/l and 0.67 g/l respectively. The stimulating effects of organic and inorganic factors on the bacterial growth and SCP production was also tested. Addition of inorganic nutrients such as potassium phosphate (0.05%), magnesium sulphate (0.01%), and organic nutrient in the form of yeast extract (0.1%) to the fermentation medium slightly promoted the bacterial growth which reflected positively on SCP production and the percentage of the consumed crude oil, (>57%) at final pH value of 8.0. The obtained results indicated that the isolated Pseudomonas aeruginosa posses the ability to utilize the crude oil and use it as a carbon for bacterial growth and production of SCP.
Keywords: 2. Zero hunger